Study of sleep disturbances in patients with type 2 diabetes mellitus complicated by a painful form of diabetic peripheral neuropathy (Journal of Universal Science Research, 2023)
This article examines the sleep quality of patients with type 2 diabetes mellitus (T2DM), complicated by a painful form of diabetic polyneuropathy (DPN). Sleep disturbances occur in 50-80% of patients with chronic pain, and the severity of sleep disturbances depends on the intensity of the pain. Sleep disorders and neuropathic pain are interrelated and should be treated simultaneously. In order to improve sleep, one of the factors influencing sleep, treatment of a painful form of DPN leads patients to improve the quality of sleep and at the same time the quality of life.